Early expression of surfactant proteins D in Fusarium solani infected rat cornea - Che, Cheng-Ye (International Journal of Ophthalmology Press, 2012)
AIM: To investigate the early expression of surfactant proteins D(SP-D) in Fusarium solani infected rat cornea. METHODS: Wistar rats were divided into group A, B and C randomly. The right eyes were chosen as the experiment one. Group A was control group. Group B was not inoculated with Fusarium solani. Group C was taken as fusarium solani keratitis model. Five rats in group B and C were executed randomly at 6, 12, 24, 48 and 96 hours respectively after the experimental model being established. The expression of SP-D was assessed through immunohistochemistry and reverse transcription polymerase chain reaction(RT-PCR). RESULTS: RT-PCR detected that the SP-D mRNA expression was low in the corneal of normal rats and group B. The expression of fungal infected cornea increased gradually and reached the peak at 24 hours in group C. The synchronous expression of group B and C were in significant difference (P<0.01). Immunohistochemisty discovered the protein of SP-D expression was increased gradually from 12 hours and reached the peak at 48 hours in group C. The synchronous expression of group B and C were also in significant difference (P<0.01). CONCLUSION: There exists SP-D in rat corneal tissue and the expression is significantly increased at the early period of fusarium solani infected cornea. SP-D may play a role in the early innate immunity response of the corneal resistance to Fusarium solani infection.